1996
DOI: 10.1002/j.1460-2075.1996.tb00548.x
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal activating and inhibitory domains determine the transactivation potential of BSAP (Pax-5), Pax-2 and Pax-8.

Abstract: Pax‐5 encodes the transcription factor BSAP which plays an essential role in early B cell development and midbrain patterning. In this study we have analysed the structural requirements for transcriptional activation by BSAP. In vitro mutagenesis and transient transfection experiments indicate that the C‐terminal serine/threonine/proline‐rich region of BSAP contains a potent transactivation domain of 55 amino acids which is active from promoter and enhancer positions. This transactivation domain was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 50 publications
5
145
3
1
Order By: Relevance
“…Carboxyl inhibitory or masking domains are common regulatory motifs observed in a number of transcription factors including PHO4, c-Myb, Pax2, Pax5, Pax8, C/EBP␤(NF-M), Nkx2.5, and Pitx2 (11,(41)(42)(43)(44)(45). The mechanism of action for these inhibitory domains varies depending on the transcription factor examined.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxyl inhibitory or masking domains are common regulatory motifs observed in a number of transcription factors including PHO4, c-Myb, Pax2, Pax5, Pax8, C/EBP␤(NF-M), Nkx2.5, and Pitx2 (11,(41)(42)(43)(44)(45). The mechanism of action for these inhibitory domains varies depending on the transcription factor examined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the Pax8 transcriptional properties showed that the C terminus of Pax8a is required for transactivation (26). In particular, the data obtained studying various Pax genes showed that the regulatory module of these proteins consisting of a potent transactivation region has been conserved among the members of the family and lies in the C-terminal region downstream amino acid 300 (26).…”
Section: Pax8 Splicing Isoforms Are Able To Reactivate Endogenous Tg mentioning
confidence: 99%
“…In particular, the data obtained studying various Pax genes showed that the regulatory module of these proteins consisting of a potent transactivation region has been conserved among the members of the family and lies in the C-terminal region downstream amino acid 300 (26). Thus the C-terminal region of Pax8, as well as that of other Pax genes, represents the only domain of the protein involved in transcriptional activation that has been identified so far.…”
Section: Pax8 Splicing Isoforms Are Able To Reactivate Endogenous Tg mentioning
confidence: 99%
“…Among them is the B-cellspecific activator protein (BSAP), which is encoded by the Pax5 gene . This transcription factor is expressed at all stages of B lymphopoiesis except in terminally differentiated plasma cells (Barberis et al 1990), recognizes DNA via its amino-terminal paired do main (Czerny et al 1993), and uses a carboxy-terminal regulatory module consisting of activating and inhibi tory sequences to control gene transcription (Dorfler and Busslinger 1996). BSAP (Pax5) has been implicated in the regulation of several B-cell-specific genes primarily based on the identification of BSAP-binding sites in their control regions.…”
mentioning
confidence: 99%